Virtual, augmented and mixed reality : applications in health, cultural heritage, and industry : 10th International Conference, VAMR 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings.: applications in health, cultural heritage, and industry : 10th International Conference, VAMR 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part II (2018) - Unknown
No abstract available